Trends in Adult and Continuing Education in Germany - Ekkehard Nuissl (Firenze University Press, 2011)
This contribution summarizes the most important trends in adult education in Germany as they were elaborated in a secondary analytic research project of the DIE (Deutsches Institut für Erwachsenenbildung - German Institute for Adult Education) in 2007. According to the study, participation in continuing education in Germany is increasing after long years of decrease, even though, overall, financing of adult education has been further reduced. Cooperation as well as competition between continuing education institutions has increased. Course offers have become shorter, counselling and information have more significant roles than in the past, and those employed in adult education, especially teaching staff, have a higher level of qualifications than before. Adult education policy in Germany has varying aims as a result of the federal structure of the country. Incentives for vocational and workplace training predominate however.